Prognostic Value of Persistent CSF Antibodies at 12 Months in Anti-NMDAR Encephalitis. - Ciano-Petersen, Nicolas Lundahl; Mélisse, Robert; Muñiz-Castrillo, Sergio; Wucher, Valentin; Klich, Amna; Alberto Vogrig, Alberto; Villagrán García, Macarena; Antonio Farina, Antonio; David Goncalves, David; Geraldine Picard, Geraldine; Veronique Rogemond, Veronique; Bastien Joubert, Bastien; et al. (American Academy of Neurology, 2023)
Background and objectives: Anti-NMDA receptor (NMDAR) encephalitis is defined by the presence of antibodies (Abs) targeting the NMDAR in the CSF. This study aimed to determine the prognostic value of persistent CSF NMDAR-Abs during follow-up. Methods: This retrospective observational study included patients diagnosed with anti-NMDAR encephalitis in the French Reference Center for Paraneoplastic Neurological Syndromes and Autoimmune Encephalitis and for whom CSF samples were obtained at diagnosis and >4 months of follow-up to evaluate CSF NMDAR-Ab persistence. Because patients were tested for CSF NMDAR-Abs at different time points, samples were stratified into different periods of follow-up (i.e., 12 months was considered for the 9- to 16-month follow-up period). Results: Among the 501 patients diagnosed with anti-NMDAR encephalitis between January 2007 and June 2020, 89 (17%) were tested between 4 and 120 months for CSF NMDAR-Abs after clinical improvement and included in the study (75/89 women, 84%; median age 20 years, interquartile range [IQR] 16-26). During follow-up, 21 of 89 (23%) patients had a relapse after a median time of 29 months (IQR 18-47), and 20 of 89 (22%) had a poor outcome (mRS ≥3) after a median last follow-up of 36 months (IQR 19-64). Most patients (69/89, 77%) were tested at the 12-month follow-up period, and 42 of 69 (60%) of them had persistent CSF NMDAR-Abs. When comparing patients with persistent or absent CSF NMDAR-Abs at 12 months, poor outcome at the last follow-up was more frequent in the former (38% vs 8%, p = 0.01), who had relapses more often (23% vs 7%), which also appeared earlier in the course of the disease (90% during the following 4 years of follow-up vs 20%), although no significant difference was observed at long-term follow-up (p = 0.15). In addition, patients with persistent CSF NMDAR-Abs at 12 months had higher titers of CSF NMDAR-Abs at diagnosis
Keywords: Encefalitis; NMDA receptor; antibodies